Correlation among the nuclear structure and effective symmetry energy of finite nuclei - Naz, Tabassum; Bhuyan, Mrutunjaya; Ahmad, Shakeb; Patra, S.K.; Abusara, H. (Elsevier, 2019)
The structural evolution and correlation of ground state properties with the effective nuclear matter characteristics for the even-even isotopes of Th and U nuclei are investigated within axially and triaxially deformed Relativistic-Hartree-Bogoliubov approaches. The density dependent meson exchange (DD-ME), point coupling (DD-PC)and non-linear (NL3 ⁎ )force parameters are used for the present analysis. The potential energy surface is calculated by the quadratic constraint method to analyze the structural evolution by mean of shape transitions over an isotopic chain. The Coherent Density Fluctuation Model is used to formulate the nuclear matter characteristics such as symmetry energy and neutron pressure by weightening the density for finite nuclei. Further, we have predicted the possible modes of decay (α-decay and/or β-decay)in order to understand the stability of these nuclei. The calculated results are compared with experimental and other theoretical models, wherever available. We found a peak for effective symmetry energy and neutron pressure at N=150 for all the force parameters, which may correlate with the shell/sub-shell closures in an isotopic chain. © 2019 Elsevier B.V.